The Internationalisation of Higher Education – Strategic Approaches, Outcomes and Implications - Dalton, J A (2010)
There are several contemporary debates in the academic literature which surround internationalisation in higher education; these include strategies implemented, the outcomes of internationalisation as well as the implications of internationalisation on the quality of higher education. This research project looks at the strategic approaches, outcomes and implications of internationalisation in British higher education. This was done by interviewing high ranking individuals at top tier institutions through a semi structured interview process. The findings of this investigation show that the positives of internationalisation include increased international recruitment, increased quality of education, and increased brand exposure. The key negative outcome from the process was indicated by all institutions to be the increasingly turgid nature of the UK immigration system and the problems associated with this. The overall feeling was that internationalisation was on the whole progressive and set institutions up well for the future increasing the competitive edge despite the negative outcomes. Future research should be conducted on the effects of capping immigration and student visas which is currently the biggest issue facing British institutions invested in international markets.